Economic growth: from endogenous growth to the new role of economic policies (Cultura Económica, 2019)
Economic growth has been the subject of an extended debate oriented towards the formulation of a theory to explain it. Ernesto O’Connor shows in his article the theoretical contributions of the last twenty years and compares them with the strategies for economic development used during the same period. The author maintains that, even though there is important research work on the causes of economic growth, there is still no real agreement about the ideal policies to seek in order to reach it. O’Connor believes that technology and human capital are determinant for growth, but he also thinks that investment and institutions should be considered as important factors.
Keywords: economic growth; technology; human capital; investmentinstitutions